TOI-132 b: A short-period planet in the Neptune desert transiting a V = 11.3 G-type star. Issue 1 (29th January 2020) - Díaz, Matías R; Jenkins, James S; Gandolfi, Davide; Lopez, Eric D; Soto, Maritza G; Cortés-Zuleta, Pía; Berdiñas, Zaira M; Stassun, Keivan G; Collins, Karen A; Vines, José I; Ziegler, Carl; Fridlund, Malcom; et al.
ABSTRACT: The Neptune desert is a feature seen in the radius-period plane, whereby a notable dearth of short period, Neptune-like planets is found. Here, we report the Transiting Exoplanet Survey Satellite ( TESS ) discovery of a new short-period planet in the Neptune desert, orbiting the G-type dwarf TYC 8003-1117-1 (TOI-132). TESS photometry shows transit-like dips at the level of ∼1400 ppm occurring every ∼2.11 d. High-precision radial velocity follow-up with High Accuracy Radial Velocity Planet Searcher confirmed the planetary nature of the transit signal and provided a semi-amplitude radial velocity variation of 11.38 ^+0.84_-0.85 m s −1, which, when combined with the stellar mass of 0.97 ± 0.06 M⊙, provides a planetary mass of 22.40^+1.90_-1.92 M ⊕ . Modelling the TESS light curve returns a planet radius of 3.42^+0.13_-0.14 R ⊕, and therefore the planet bulk density is found to be 3.08^+0.44_-0.46 g cm −3 . Planet structure models suggest that the bulk of the planet mass is in the form of a rocky core, with an atmospheric mass fraction of 4.3^+1.2_-2.3 per cent. TOI-132 b is a TESS Level 1 Science Requirement candidate, and therefore priority follow-up will allow the search for additional planets in the system, whilst helping to constrain low-mass planet formation and evolution models, particularly valuable for better understanding of the Neptune desert.